MeCP2 Lactylation Protects against Ischemic Brain Injury by Transcriptionally Regulating Neuronal Apoptosis - Min Sun; Yuxin Zhang; Rui Mao; Yan Chen; Pinyi Liu; Lei Ye; Siyi Xu; Junqiu Jia; Shu Shu; Huiya Li; Yanping Yin; Shengnan Xia; et al. (Advanced Science)
Abstract Lactate plays diverse roles in brain pathophysiology, including ischemic stroke. Here, the role of lysine lactylation, an epigenetic modification of lactate, in cerebral ischemia is investigated. Using a mouse model of transient middle cerebral artery occlusion, increased brain lactate levels and global protein lactylation are observed. Proteomics analysis reveals significant lactylation of non‐histone proteins in the ischemic penumbra. Lactylation of MeCP2, a transcriptional regulator, is identified as a protective mechanism against stroke‐induced neuronal death. Inhibition of MeCP2 lactylation through chemical or genetic manipulation increases infarct volume and aggravates neurological deficits. Mechanistically, MeCP2 lactylation at K210/K249 represses the transcription of apoptosis‐associated genes, including Pdcd4 and Pla2g6, thereby attenuating neuronal apoptosis. Additionally, HDAC3 and p300 are identified as key enzymes that regulate MeCP2 lactylation post‐stroke. The findings suggest that MeCP2 lactylation offers a potential therapeutic target for alleviating neuronal damage and improving stroke outcomes.